«Ogne generacion d'animal»: incursioni animali nell'itinerario di «Huon d'Auvergne» (Carte Romanze, 2025)
In the chanson de geste of Huon d’Auvergne, the eponymous hero is forced by Charles Martel to travel to Hell to demand tribute from Lucifer. Huon’s wandering is accomplished through known places and unknown, fantastic places, before he reaches the entrance to Hades. In the transition from known to fantastic geography, the chanson de geste became populated with a rich and diverse fauna. Many animals, in fact, will be found on the paladin’s path before he reaches Hell. These animals play a precise role in the development of the narrative, as an indication of a progressive approach to Hell. In the contribution, a complete survey of the fauna encountered by Huon will be offered and an attempt will be made to analyse the meaning of the encounters, both individually and from the perspective of the epic narrative.
Keywords: Huon d'Auvergne; epic; Franco-Italian; Middle Ages